PENTINGNYA PEMBERIAN ASI EKSLUSIF UNTUK MENCEGAH TERJADINYA STUNTING PADA BALITA: LITERATUR REVIEW - Sihab Sihab; Miftahul Falah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Stunting is an indicator of linear growth failure caused by chronic malnutrition, repeated infections, and low stimulation in early life. This condition has long-term impacts on child development, including cognitive impairment, the risk of chronic disease, and decreased productivity in adulthood. One of the main protective factors in preventing stunting is exclusive breastfeeding for the first six months of life. This literature review aims to analyze the relationship between exclusive breastfeeding and stunting incidence based on five articles published between 2014 and 2023. A literature search was conducted through the Google Scholar database using the keywords "exclusive breastfeeding," "stunting," "toddler," and "nutritional status." The inclusion criteria yielded five articles that were analyzed using the PRISMA guidelines. The analysis showed that all articles found a significant association between not being exclusively breastfed and an increased risk of stunting, with a p-value <0.05. One study showed an Odds Ratio (OR) of 61, confirming the high risk of stunting in children who do not receive exclusive breastfeeding. Furthermore, maternal education, socioeconomic factors, and early provision of complementary feeding also increase the risk of stunting. This literature review emphasizes the importance of ongoing education and support regarding exclusive breastfeeding practices to reduce the prevalence of stunting in Indonesia